ESTIMATION OF EFFICIENCY OF USE OF CONTROL AND TEST STATIONS - Юрій Борисович Прібилєв (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
Indicator of estimating the effectiveness of anti-aircraft missiles with the help of test stations was suggest in the article. The article describes the expression takes the cost of losses for erroneous decisions during control, and the quality characteristics of test stations. The possible ways of ensuring the specified technical readiness of anti-aircraft missiles are investigated: increasing the reliability of anti-aircraft missiles and creating missiles that are being restored during operation and providing the necessary technical readiness of anti-aircraft missiles together with test stations. Expressions are proposed for calculating costs in the implementation of these ways to ensure the specified technical readiness of anti-aircraft missiles. The quantitative values of the effectiveness of control of anti-aircraft missiles with the help of test stations can be calculated and allow us to make a comparative analysis of the effectiveness of the use of the developed promising universal test stations, to identify rational design solutions and to improve them. These technological advantages make it possible to build a promising universal unified reconfigurable automated control and test station. This makes it possible to diagnose bugs of all types of missiles of the Armed Forces of Ukraine.